How to Overcome the Risk of Islamic Banks: Evidence from Indonesia - Suganda, Asep Dadan; Anita, Anita; Wulandari, Soliyah (El-Barka Journal of Islamic Economics and Business, 2023)
Risk management is a crucial aspect of Islamic banking to ensure the sustainability and operational safety of banks and maintain the trust of customers and stakeholders. This article discusses the importance of risk management in the context of Islamic banking and analyzes the challenges faced by Islamic banks in managing risks. This research adopts a qualitative approach, with a focus on collecting in-depth descriptive and interpretative data. The study involves text analysis and case studies of Islamic banks in Indonesia. This article discussed the basic concepts of risk management in the context of Islamic banks, including risk identification, risk evaluation, and risk control. We explain the importance of comprehensive risk assessment and the use of appropriate risk management tools to address specific risks faced by Islamic banks. By analyzing these challenges, this article provides a comprehensive overview of risk management in Islamic banking and offers recommendations to enhance the capabilities of Islamic banks in effectively managing the risks. Finally, the author offers a model for overcoming the risk of Islamic banks with the Hexagonal Model consisting of two sides (internal and external) and six main cores: Education, Identification, Accountable, Guidelines, Research, and Technology.